Cost analysis of education for students in the School of Health of Alborz University of Medical Sciences: An application of activity-based costing technique - Behrooz Pouragha; Mehdi Tayebi Arasteh; Ehsan Zarei; Mahdieh Abdolahi; Hojjat Sheikhbardsiri (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: The educational service is expensive and having the right financial information is one of the most important tools for managing financial resources. Therefore, due to the importance of this issue, this study aimed to determine the cost of educational services for medical sciences students at Alborz University of Medical Sciences. METHODOLOGY: A cross-sectional study was conducted between March 20, 2018, and March 20, 2019, at Alborz University of Medical Sciences. The current and capital cost data were extracted from the university's financial database, and the cost price of services provided was calculated using the activity-based cost model. RESULTS: The mean annual cost of services per student was $4778, and the mean cost of education per hour was $113. The total cost price of services provided per student at the school was 65% for wages and salary, 26% for depreciation of building and equipment, and 9% for consumable goods and services. Furthermore, the share of different cost centers to the total cost price of services provided per student was 82% for educational services, 11.9% for student welfare services, and 6.1% for research services. CONCLUSION: Costs of personnel, especially pays to faculty members and the costs of capital expenditures, are the most important costs in higher education institutions. It seems reducing of pay to faculty members through novelty approach of education and evaluation, reducing capital expenditures through use effective of buildings and equipment that can be placed higher education institutions in the path to productivity.